PENGARUH KONDISI DAN LAMA PENYIMPANAN PADA SUHU RUANG DAN REFRIGERATOR TERHADAP ANGKA TOTAL PLATE COUNT (TPC) SAMPEL SEI BABI DARI 4 TOKO DI KOTA KUPANG - Erda Eni Rame Hau; Eny Rohyati (Partner, 2018)
This study aims to evaluate the effect of different storage conditions and duration to the growth and development of microorganisms and pathogens up to a certain interval time. Therefore, the research will look at how the growth of bacteria in Se’i pork will be seen through the Total Total Count (TPC) in the condition of room temperature and refrigerator up to 5 days of storage time intervals. By treating the room temperature and temperature of the refrigerator with a storage time of 0, 1, 2, 3, 4, and 5 days, the microorganism numbers will be obtained in these two different storage conditions for 5 days.  The results showed clear result of the growth rate and the number of bacteria between Se’I stored at therefrigerator temperature storage with Se’I at room temperature every day.  It is clear from the results that the growth of microorganisms greater in Se'i at room temperature compared to those refrigerated. Other results found that samples from one shop have already shown TPC number above the maximum standard for the total number of microorganisms allowed by Standar Nasional Indonesia (SNI) in smoked meat.